EPISTEMOLOGICAL QUESTIONS: THE RELATIONSHIP OF SENSING, REASON, INTUITION, AND REVELATION IN THE BUILDING OF ISLAMIC SCIENCE - Asriana, Asriana; Ok, Azizah Hanum (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The purpose of writing this article is to find answers related to epistemological questions: the relationship of sense, reason, intuition, and revelation in the development of Islamic science. The research method used is library research. The data collection technique used by researchers is a literature study. The library method is research carried out by reading books or magazines with other data sources in the library. The results of this research found that epistemology in seeking knowledge originates from Empiricism, Rationalism, and Intuition-Revelation. Judging from the basic teachings of Islam, the Koran is knowledge obtained through the senses, reason, and heart. The senses, reason, and heart play a role in distinguishing truth from falsehood. Reason is considered a source of thinking and philosophizing with the aim of pursuing truth. Revelation provides an explanation to explore the truth. Reason is considered a tool capable of rationally expressing the truth brought by revelation. In Islamic teachings, the use of reason is not given absolute freedom. The suggestion for the next writer is that it is deemed necessary to develop the range of reason in finding truth based on the kauniyah verses.